Welfare versus market access: The implications of tariff structure for tariff reform - James E. Anderson; James Peter Neary (University College Dublin, Department of Economics, 2004)
We show that the effects of tariff changes on welfare and import volume can be fully characterised by their effects on the generalised mean and variance of the tariff distribution. Using these tools, we derive new results for welfare- and market-access-improving tariff changes, which imply two cones of liberalisation in price space. Because welfare is negatively but import volume positively related to the generalised variance, the cones do not intersect, which poses a dilemma for trade policy reform. Finally, we show that generalised and trade-weighted moments are mutually proportional when the trade expenditure function is CES.
hdl:10197/1266
Keywords: F13; F15; 330; Concertina rule; Market access; Piecemeal policy reform; Tariff moments; Uniform tariff reductions; Zollpolitik; Wohlfahrtsanalyse; Importbeschränkung